Topological Comparison of Dual-Input DC-DC Converters - A. Lavanya; K. Vijaya Kumar; J. Divya Navamani (Institute of Advanced Engineering and Science, 2017)
Dual input dc-dc converters have two input voltage sources or one input source and an energy storage system like ultra capacitor, PV, battery, super capacitors and a single output load. In order to process the power in hybrid energy systems using reduced part count, researchers have proposed several multi-input dc-dc power converter topologies to transfer power from different input voltage sources to the output. This paper compares non-isolated dual-input converter topologies topologically ,based on the components count, various fields of application and different modes of operation for hybrid systems mainly used in electric vehicles and renewable energy systems composed of energy storage systems (ESSs) with different voltage-current characteristics. Dual input dc-dc converter topologies considered in this paper are investigated using MATLAB and PSIM software and output voltage and inductor current waveforms are shown.